Impact on Utilization and Shift in Treatment Needs Post-COVID Lockdown of Pediatric Dentistry in a Tertiary Care Hospital - Nandlal, Bhojraj; Singh, Birti; Gopi, Arun (Frontiers in Dental Medicine, 2021)
Background: The COVID-19 pandemic has brought all treatments other than emergencies to a halt. Dental disease, being a multifactorial microbial disease, is capable of progressing to pulpits and its sequelae. The purpose of this study is to predict the impact of utilization of dental services and the progression of treatment needs in children during the lockdown and partial lockdown. Methods: Outpatient department data from the year 2017–2019 from the Department of Pediatric and Preventive Dentistry, JSS Dental College was collected. A table of treatments provided was prepared. Utilization of services as care-seeking rates at 10, 25, and 50% were assumed and modeled corresponding to each stage of the lockdown using linear regression analysis. Dental caries progression was calculated as shifts in treatment needs from permanent restorations to temporary restorations, pulpectomies, or extraction, assuming a 10% progress to each sequela. Results: The p-values for 10, 25, and 50% care-seeking rates were 0.021, <0.001, and <0.001, respectively. Conclusion: The number and severity of cases were predicted to have increased. However, after removal of lockdown, it was noted that the number of patients seeking care was significantly less. The advancement in progression of dental disease further adds to the burden of society and caregivers.